Merger Mechanisms - Sandro Brusco; Giuseppe Lopomo; S. Viswanathan (Fondazione Eni Enrico Mattei (FEEM), 2004)
A firm can merge with one of n potential partners. The owner of each firm has private information about both his firm's stand-alone value and a component of the synergies that would be realized by the merger involving his firm. We characterize incentive-efficient mechanisms in two cases. First, we assume that the value of any newly formed partnership is verifiable, hence transfers can be made contingent on the new information accruing after the merger. Second, we study the case of uncontingent rules. In the first case, we show that it is not optimal, in general, to redistribute shares of non-merging firms, and identify necessary and sufficient conditions for the implementability of efficient merger rules. In the second case, we show that the first-best can be obtained i) always, if the synergy values are privately known but the firms' stand-alone values are observable; ii) only with sufficiently large synergies, if the firms' stand-alone are privately known; and iii) never, if the set of feasible mechanisms is restricted to auctions in shares.
Keywords: C72; D44; G34; 330; Mechanism design; Merger; Fusion; Asymmetrische Information; Theorie; Unternehmenswert